Atrio-oesophageal fistula following atrial fibrillation ablation: how to manage this dreaded complication?. (27th July 2021) - Moiroux-Sahraoui, Alexander; Manceau, Gilles; Schoell, Thibaut; Combes, Alain; Bouglé, Adrien; Leprince, Pascal; Vaillant, Jean Christophe; Lebreton, Guillaume
Abstract: : OBJECTIVES: Atrio-oesophageal fistula is a rare but serious complication of radiofrequency catheter ablation of atrial fibrillation. Therapeutic options are surgery, oesophageal stenting and conservative treatment (antibiotics and anticoagulation). However, there are no guidelines available. Since no article dwells on the technical considerations of this surgery, we aim to present here our experience and share our surgical approach. METHODS: Between January 2012 and March 2020, all consecutive patients treated for atrio-oesophageal fistula following radiofrequency catheter ablation of atrial fibrillation at our institution were analysed retrospectively. The diagnosis was made on a set of clinical and radiological signs. All patients benefitted from a combined approach involving both digestive and cardiac surgeons. Femoro-femoral peripheral cardiopulmonary by-pass was used. The surgical approach was a right posterolateral thoracotomy. Atrial repair was done on fibrillating heart without cross-clamping, using a left atriotomy. Digestive management consisted of a total oesophagectomy. RESULTS: We identified 6 patients with this complication. The median age was 53 [34–72] years. Symptoms were neurological symptoms, fever and chest pain. Diagnostic modalities were cerebral imaging, chest CT and transthoracic echocardiogram. Atrial repair consisted in a suture of the atrium or by using a pericardial patch. With a median follow-up of 3.1 [0.1–7.7] years, only one patient died during the follow-up. CONCLUSIONS: Our experience shows that an aggressive surgery with a large resection of the oesophagus and left atrial repair by right thoracotomy in the same time provides good results. The ability to involve simultaneously both experienced digestive and cardiac surgical teams is the key for this strategy. Abstract : Treatment of atrial fibrillation (AF) involves anticoagulation, heart rate control and heart rhythm control.